The new entrepreneurs : how race, class, and gender shape American enterprise - Valdez, Zulema (Stanford University Press, 2011)
For many entrepreneurs, the American Dream remains only partially fulfilled. Unequal outcomes between the middle and lower classes, men and women, and Latino/as, whites, and blacks highlight continuing inequalities and constraints within American society. With a focus on a diverse group of Latino entrepreneurs, this book explores how class, gender, race, and ethnicity all shape Latino entrepreneurs' capacity to succeed in business in the United States. Bringing intersectionality into conversation with theories of ethnic entrepreneurship, Zulema Valdez considers how various factors create, maintain, and transform the social and economic lives of Latino entrepreneurs.